Description of a new genus and thirteen new species of Ctenidae (Araneae, Ctenidae) from the Chocó region of Ecuador - Dupérré, Nadine (Zootaxa, 2015)
The genus Chococtenus n. gen. is established for a group of Ctenidae with a unique ventral and spine-like retrolateral tibial apophysis, primarily found in the Chocó-Tumbes-Magdalena corridor. Thirteen new species are described: Chococtenus otonga n. sp., C. neblina n. sp., C. cuchilla n. sp., C. fantasma n. sp., C. waitti n. sp., C. cappuccino n. sp., C. lasdamas n. sp., C. suffuscus n. sp., C. otongachi n. sp., C. kashakara n. sp., C. piemontana n. sp., C. luchoi n. sp. and C. duendecito n. sp. Ctenus acanthoctenoides Schmidt and Enoploctenus miserabilis (Strand) are transferred to Chococtenus.